A soluble SNARE drives rapid docking, bypassing ATP and Sec17/18p for vacuole fusion - Thorngren, Naomi (2004)
Membrane fusion requires priming, the disassembly of cis-SNARE complexes by the ATP-driven chaperones Sec18/17p. Yeast vacuole priming releases Vam7p, a soluble SNARE. Vam7p reassociation during docking allows trans-SNARE pairing and fusion. We now report that recombinant Vam7p (rVam7p) enters into complex with other SNAREs in vitro and bypasses the need for Sec17p, Sec18p, and ATP. Thus, the sole essential function of vacuole priming in vitro is the release of Vam7p from cis-SNARE complexes. In ‘bypass fusion', without ATP but with added rVam7p, there are sufficient unpaired vacuolar SNAREs Vam3p, Vti1p, and Nyv1p to interact with Vam7p and support fusion. However, active SNARE proteins are not sufficient for bypass fusion. rVam7p does not bypass requirements for Rho GTPases,Vps33p, Vps39p, Vps41p, calmodulin, specific lipids, or Vph1p, a subunit of the V-ATPase. With excess rVam7p, reduced levels of PI(3)P or functional Ypt7p suffice for bypass fusion. High concentrations of rVam7p allow the R-SNARE Ykt6p to substitute for Nyv1p for fusion; this functional redundancy among vacuole SNAREs may explain why nyv1Δ strains lack the vacuole fragmentation seen with mutants in other fusion catalysts.